Needle in a haystack—genetic evidence confirms the expansion of the alien echinoid Diadema setosum (Echinoidea: Diadematidae) to the Mediterranean coast of Israel - Bronstein, Omri; Kroh, Andreas (Zootaxa, 2018)
Diadema setosum (Leske, 1778), a widespread tropical echinoid and key herbivore in shallow water environments is currently expanding in the Mediterranean Sea. It was introduced by unknown means and first observed in southern Turkey in 2006. From there it spread eastwards to Lebanon (2009) and westwards to the Aegean Sea (2014). Since late 2016 sporadic sightings of black, long-spined sea urchins were reported by recreational divers from rock reefs off the Israeli coast. Numerous attempts to verify these records failed; neither did the BioBlitz Israel task force encounter any D. setosum in their campaigns. Finally, a single adult specimen was observed on June 17, 2017 in a deep rock crevice at 3.5 m depth at Gordon Beach, Tel Aviv. Although the specimen could not be recovered, spine fragments sampled were enough to genetically verify the visual underwater identification based on morphology. Sequences of COI, ATP8-Lysine, and the mitochondrial Control Region of the Israel specimen are identical to those of the specimen collected in 2006 in Turkey, unambiguously assigning the specimen to D. setosum clade b. This lends support to the hypothesis of a single introduction event and fits well with the habitat suitability and distribution model for D. setosum published recently. The more rapid and larger range extension along a south-eastern, counter-current trajectory may reflect a strong habitat preference for D. setosum in this area of the Levantine Basin as predicted by the model.